Data for Long term stability of c-Si surface passivation using corona charged SiO2 - Bonilla, R (University of Oxford, 2017)
Raw data embedded in Matlab figure files for Photo-conductance Decay effective lifetime measurements, luminescence measurements, and Kelvin Probe Measurements.